A POC device for on-the-spot detection of hexavalent chromium in wastewater. Issue 5 (October 2020) - Kumar, Nitesh; Madhwal, Devinder; Jain, V.K.; Suman,
Graphical abstract: Highlights: A hand-held portable, point of care (POC) device for detection of Chromium in liquid medium. The method involves the detection of hexavalent chromium in water as well as biological samples using citrate-capped silver nanoparticle (C-AgNPs) leading to reduction of Cr(VI) to Cr (III). The device was tested and results were calibrated with flame AAS. The limit of detection (LOD) and limit of quantitation (LOQ) is 26 ppb and 79 ppb, respectively. Abstract: The present work describes a novel handheld pocket-friendly device for on the spot detection of chromium. The device gives not only qualitative but also the quantitative determination of chromium in environmental wastewater samples. The qualitative detection can be made visually by the naked eye while for the quantitative detection a colorimetric device has been fabricated in-house. The system comprises a source, sample holder, detector, and a microcontroller-processing unit with a display unit. The method involves the detection of hexavalent chromium Cr (VI) in aqueous systems by using citrate-capped silver nanoparticle (C-AgNPs) leading to a reduction of Cr (VI) to Cr (III). The citrate capped silver nanoparticles were synthesized and characterized using a blend of characterization techniques like ultra-violet visible (UV-Vis) spectrophotometry, scanning electron microscopy (SEM), transmission electron microscopy (TEM) and dynamic light scattering (DLS) techniques. The device performance remained unaffected even in the presence of various interfering cations present in the wastewater. The device was tested, and results were calibrated with standard atomic absorption spectroscopy (AAS), it showed linearity from 0.01-0.7 ppm for wastewater samples tested with spiking different known concentrations of chromium. The limit of detection (LOD) of the method is 26 ppb and the limit of quantitation (LOQ) of 79 ppb. The development of a low-cost, simple colorimeter employing the same sensor principle underlines the on-site applicability of this method.